2005
DOI: 10.1002/ajpa.20080
|View full text |Cite
|
Sign up to set email alerts
|

Metric dental variation of major human populations

Abstract: Mesiodistal and buccolingual crown diameters of all teeth recorded in 72 major human population groups and seven geographic groups were analyzed. The results obtained are fivefold. First, the largest teeth are found among Australians, followed by Melanesians, Micronesians, sub-Saharan Africans, and Native Americans. Philippine Negritos, Jomon/Ainu, and Western Eurasians have small teeth, while East/Southeast Asians and Polynesians are intermediate in overall tooth size. Second, in terms of odontometric shape f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
145
1
16

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 166 publications
(185 citation statements)
references
References 54 publications
23
145
1
16
Order By: Relevance
“…An interesting discordance are the rather low values of tooth size variables in African groups (San and Khoe). Hanihara and Ishida (2005) have reported that sub-Saharan African groups are characterized by relatively large tooth dimensions, but our results did not reflect that. This could be due to the fact that these groups were substantially underrepresented in terms of number of analyzed individuals, which could greatly impact our results.…”
Section: Intergroup Variationcontrasting
confidence: 99%
See 3 more Smart Citations
“…An interesting discordance are the rather low values of tooth size variables in African groups (San and Khoe). Hanihara and Ishida (2005) have reported that sub-Saharan African groups are characterized by relatively large tooth dimensions, but our results did not reflect that. This could be due to the fact that these groups were substantially underrepresented in terms of number of analyzed individuals, which could greatly impact our results.…”
Section: Intergroup Variationcontrasting
confidence: 99%
“…This inconsistency suggests that genetic factors determine dental size, rather than external or environmental influences (Dempsey et al, 1999;Garn et al, 1977). Australian Aborigines, Native Americans, and Eskimos were reported to have relatively large teeth and the Negritos (Agta) some of the smallest (Hanihara and Ishida, 2005), which is in accord with our results.…”
Section: Intergroup Variationsupporting
confidence: 88%
See 2 more Smart Citations
“…[1][2][3][4] They have focused on differences among populations and differences among individuals within populations. Owing to their work, we now know that dental morphology is highly differentiated among human populations.…”
Section: Introductionmentioning
confidence: 99%